Dacomitinib and gedatolisib in combination with fractionated radiation in head and neck cancer. (January 2021) - Wilson, George D.; Wilson, Thomas G.; Hanna, Alaa; Dabjan, Mohamad; Buelow, Katie; Torma, John; Marples, Brian; Galoforo, Sandra
Highlights: We evaluated radiation with dual EGFR and PI3K targeting in head and neck cancer. Dacomitinib, showed an inverse correlation between growth inhibition and EGFR expression. Gedatolisib was effective in each cell line. Neither drug caused radiosensitization in vitro . Gedatolisib was relatively ineffective in vivo in combination with dacomitinib and/or radiation. Dacomitinib was highly effective alone and in combination with radiation and/or gedatolisib. Immunoblotting studies in vivo mirrored the effects seen with growth delay. Abstract: Background and purpose: There has been little success targeting individual genes in combination with radiation in head and neck cancer. In this study we investigated whether targeting two key pathways simultaneously might be more effective. Materials and methods: We studied the effect of combining dacomitinib (pan-HER, irreversible inhibitor) and gedatolisib (dual PI3K/MTOR inhibitor) with radiation in well characterized, low passage xenograft models of HNSCC in vitro and in vivo . Results: Dacomitinib showed differential growth inhibition in vitro that correlated to EGFR expression whilst gedatolisib was effective in both cell lines. Neither agent radiosensitized the cell lines in vitro. In vivo studies demonstrated that dacomitinib was an effective agent alone and in combination with radiation whilst the addition of gedatolisib did not enhance the effect of these two modalities despite inhibiting phosphorylation of key genes in the PI3K/MTOR pathway. Conclusions: Our results showed that combining two drugs with radiation provided no added benefit compared to the single most active drug. Dacomitinib deserves more investigation as a radiation sensitizing agent in HNSCC.